Anti-Bacterial Activity of Etanolic Extract and Essential Oil of Basil (Ocimum sanctum) on Growth Staphylococcus aureus Salmonella thypii and Eschericia coli - Perwitasari, Melania; Anindita, Reza; Beandrade, Maya Uzia; Nathalia, Dede Dwi; Hasmar, Wahyu Nuraini; Putri, Intan Kurnia (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2023)
Antimicrobial resistance is one of the biggest health problems. Indonesia is a country with a positive high number of E. coli (71%) Extended Spectrum Beta Lactamase (ESBL) in the Asia Pacific. Many studies report that essential oils and extracts from several species of Ocimum have antimicrobial activity against gram-positive and negative bacteria. Antibacterial activity is related to active compounds contained in plants that are also affected by the place of growth, harvesting and post-harvesting. Research related to the activity of basil (Ocimum sanctum) that already exists does not provide complete and comprehensive data related to where to grow, harvest and post-harvest basil leaves. Basil leaves that have been set parameters for growth, harvest and post-harvest processes are extracted using maceration method with 70% etanol solvent and distilled to obtain essential oils (EO). Etanolic extract (EE) and EO were tested for their activity against Escherichia coli, Staphylococcus aureus and Salmonella thypii bacteria. The results showed that the basil leaves obtained from Margahayu sub-district, East Bekasi, had a dry simplicia yield of 12.8% ± 1.5, yield of EE 16.9% ± 1.6, EO content of 0.56%. The etanolic extract of basil leaves contains alkaloids, saponins, tannins, phenolics, flavonoids, glycosides, triterpenoids and steroids. The conclusion from the results of this study is the etanol extract and essential oils of basil leaves can inhibit the growth of bacteria, both basile leaves. The inhibition zone diameter is higher in gram positive bacteria (S. aureus) than gram negative bacteria (S. thypii and E. coli).